Adaptation and evolution of freshwater Anammox communities treating saline/brackish wastewater. (1st December 2021) - Lin, Limin; Pratt, Steven; Li, Zhiheng; Ye, Liu
Highlight: Anammox reactors were stably running over 425 days under salinities of 2 (R1), 8 (R2) and 12 (R3) g NaCl/L. After long-term operation, the dominant Anammox species in R2 and R3 shifted from Ca. Brocadia sp. to Ca. Kuenenia sp. . In R2 and R3, Ca. Brocadia sp. could not recover activity and stoichiometry to its optimal levels. The activities and stoichiometries of R2 and R3 gradually recovered with the growth of Ca. Kuenenia sp.. Abstract: The most common way to apply Anammox for saline wastewater treatment is via salt adaptation of freshwater Anammox bacteria (FAB). To better apply this process in practice, it's essential to understand the salt adaptation process of FBA, as well as the underlying mechanisms. This study investigated the long-term salt adaptation process of a fixed-film FAB culture in three reactors (namely R1–R3), under salinities of 2, 8, and 12 NaCl g/L, correspondingly. All three reactors were under stable operation and achieved 80–90% total inorganic nitrogen removal efficiency throughout the 425-day operation period. R1 servers as a blank control, based on the clear microbial community shifts in R2 and R3, the operation period was divided into 2 phases. During Phase 1, all FAB in the three reactors belonged to Ca. Brocadia sp. . The Anammox activity (AA) and the ratio of nitrite/ammonium (NO2 − -N/NH4 + -N) consumption in R2 and R3 decreased with the increase of salinity and did not recover to the initial levels. During Phase 2, the relative abundance of Ca. Kuenenia sp. in R2 and R3 increased from nearly 0 to about 60 and 77%, respectively. With the growth of Ca. Kuenenia sp., the AA and stoichiometry of R2 and R3 gradually recovered. AA of R2 and R3 both reached 1.0 g NH4 + -N/L/day at the end of this phase, which was about 80% of that in R1. These results indicated that the salt adaptation of FAB culture was achieved by species shift from a low salt-tolerance one to a high salt-tolerance one. Graphical abstract: Image, graphical abstract